2016
DOI: 10.1128/aem.01702-16
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon Oil Inhibits Shiga Toxin Type 2 Phage Induction and Shiga Toxin Type 2 Production in Escherichia coli O157:H7

Abstract: This study evaluated the inhibitory effect of cinnamon oil against Escherichia coli O157:H7 Shiga toxin (Stx) production and further explored the underlying mechanisms. The MIC and minimum bactericidal concentration (MBC) of cinnamon oil against E. coli O157:H7 were 0.025% and 0.05% (vol/vol), respectively. Cinnamon oil significantly reduced Stx2 production and the stx 2 mRNA expression that is associated with diminished Vero cell cytotoxicity. Consistently, induction of the Stx-converting phage where the stx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 67 publications
(91 reference statements)
3
28
0
Order By: Relevance
“…The authors also observed that a concentration-dependent effect was observed after increasing the concentration of both oregano EO and carvacrol from 0.05 to 0.08 µL/mL, especially for luxS expression. Another relevant outcome was reported by Sheng et al [29]. In this case, the authors observed that cinnamon EO down-regulated hfq, luxS, qseB, qseC, and stx2 when adding 0.75 MIC in the culture medium.…”
Section: Regulation Of Virulence-related Genesmentioning
confidence: 58%
“…The authors also observed that a concentration-dependent effect was observed after increasing the concentration of both oregano EO and carvacrol from 0.05 to 0.08 µL/mL, especially for luxS expression. Another relevant outcome was reported by Sheng et al [29]. In this case, the authors observed that cinnamon EO down-regulated hfq, luxS, qseB, qseC, and stx2 when adding 0.75 MIC in the culture medium.…”
Section: Regulation Of Virulence-related Genesmentioning
confidence: 58%
“…In addition, oregano essential oil and its main active ingredient, carvacrol, also significantly downregulate the stx gene at a very low sub‐MIC concentration (0.005%), and the luxS gene is also significantly downregulated (Mith, Clinquart, Zhiri, Daube, & Delcenserie, 2015). Moreover, sub‐MIC of cinnamon reduces the Shiga toxin of E. coli O157:H7 to an undetectable level, which may be due to the decreased amounts of Stx2‐converting phage by blocking phage lytic cycle (Sheng, Rasco, & Zhu, 2016).…”
Section: Bacterial Toxinsmentioning
confidence: 99%
“…The EOs' inhibitory capacity is generally due to their ability to degrade and damage cellular walls, cell membranes, and membrane proteins, enhancing the cell membrane permeability and leading to the escape of bacterial cell contents [36]. Moreover, EOs have also shown antimicrobial activity against pathogenic E. coli due to their inhibitory effects on biofilm formation and on major virulence factors, such as shiga toxin, through the inhibition of shiga toxin encoding genes and through phage induction and production [37,38].…”
Section: Resultsmentioning
confidence: 99%